Service life prediction method for wheel-hub-bearing under random multi-axial wheel loading. (April 2021) - Zhao, Li-Hui; Li, Qi-Chen; Feng, Jin-Zhi; Zheng, Song-Lin
Graphical abstract: Highlights: Considering the angular misalignment of bearing ring, the calculation model of bearing contact load is established. The life damage of wheel-hub-bearing unit is calculated by random road load based on proving ground. A new and more accurate prediction method for bearing service life is presented. Abstract: In view of the problem that the current bearing life evaluation is mainly based on the constant load condition, and the dynamic coupling effects of radial force, axial force and bending moment are less considered, leading to the great difference between the actual service life and the theoretical life of the bearing, this paper proposed a method of wheel-hub-bearing service life prediction under multi-axial wheel loading. Based on the data of six-dimensional force measured in the proving ground, the coupling frequency relation between multi-axis loads is determined by joint distribution counting to determine the times of damage load. Based on the deformation coordination relationship between the bearing roller and the raceway, and considering the influence of the angular misalignment of the roller, the calculation model of the instantaneous contact load of the tapered roller bearing is established. Combining the count result of joint distribution of multi-axial loads and the calculation model of contact loads, Newton-Raphson(N-R) iterative method was used to solve the bearing circumferential contact load sequence. Based on the modified L-P theory, the equivalent dynamic load of the bearing corresponding to the multi-axial load is obtained, and the validity of the results is verified by comparing with the simulation results of Romax. Combined with equivalent dynamic load of bearing, joint distribution count result and linear damage accumulation criterion, the life calculation of wheel-hub-bearing under multi-axial random road load in the proving ground was completed, and the accuracy of the results and rationality of the method were verified by bench test. Thus, it can provide reference for the design and selection of wheel-hub-bearing and life prediction.